THE ANXIETY OF INAPPROPRIATENESS SCORE - NASWIATI NASWIATI (Jurnal Evaluasi Pendidikan, 2012)
The objective of this research is to find out the effect of students perception to physic, self regulated learning, and studentsâ€™ anxiety toward the inappropriateness score test of physics. The data was collected through questionnaire and analyzed by using path analysis. The research found that as follows: 1) students perception to and studentsâ€™  anxiety had positive direct effect toward inappropriateness score test achievement, and 2) students and self-regulated learning had positive direct effect toward students anxiety.